2019
DOI: 10.1101/692830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bordetella Colonization Factor A (BcfA) elicits protective immunity againstBordetella bronchisepticain the absence of an additional adjuvant

Abstract: 15 Bordetella bronchiseptica (B. bronchiseptica) is an etiologic agent of respiratory 16 diseases in animals and humans. Despite widespread use of veterinary B. 17 bronchiseptica vaccines, there is limited information on their composition, relative 18 efficacy, and the immune responses they elicit. Furthermore, human B. bronchiseptica 19 vaccines are not available. We leveraged the dual antigenic and adjuvant functions of 20 BcfA to develop acellular B. bronchiseptica vaccines in the absence of an additional 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…It is a pseudogene in the human pathogen B. pertussis ( 29 ). We showed that BcfA is an adjuvant that elicits Th1/17 polarized T cell and antibody responses to a variety of protein antigens ( 30 , 31 ). Additionally, when combined with alum, BcfA attenuated alum primed Th2 responses.…”
Section: Introductionmentioning
confidence: 99%
“…It is a pseudogene in the human pathogen B. pertussis ( 29 ). We showed that BcfA is an adjuvant that elicits Th1/17 polarized T cell and antibody responses to a variety of protein antigens ( 30 , 31 ). Additionally, when combined with alum, BcfA attenuated alum primed Th2 responses.…”
Section: Introductionmentioning
confidence: 99%